Assessing the Impact of Regional and International Treaties on the Criminal Justice System of Pakistan: Implementation and Challenges - Dr. Rizwana Gul; Bushra Nawaz; Arooj Aziz Malik (Journal for Social Science Archives, 2025)
The present research paper takes a stock of comprehensive regional and international treaties impacting the criminal justice system of Pakistan, their ratification, implementation and the post-ratification challenges. It seeks to evaluate a select number of key treaties which bear significant implications for human rights, law enforcement practices and judicial reforms in Pakistan such as: the International Covenant on Civil and Political Rights (ICCPR), and the Convention against Torture (CAT). Using an exhaustive exegesis of legal documents, government reports and expert interviews, this paper studies Pakistani adherence to and compliance with these treaties to reveal a nuanced scenario of incomplete implementations, legislative dissonance and operational difficulties. Pakistan has made considerable advances in ratifying multiple core instruments; nonetheless, the transposing of these obligations into effective internal legal and implementation mechanisms is irregular. International legal standards cannot be implemented fully due to challenges like legislative gaps, insufficient institutional capacities and absence of awareness in judiciary and law enforcement agencies. While several illustrations of progressive legal reforms and judicial decisions in line with international commitments are identified in the research, the study shows a clear need for a more comprehensive strategy to close the implementation gap. Treaty implementation in Pakistan remains more than merely fashioning compliance with international obligations; it is vital to the development and reform of Pakistani criminal justice towards fairness, accountability, and human rights respect.